Paraneoplastic Neuromyelitis Optica Spectrum Disorder Associated With Lung Adenocarcinoma: A Case Report - Maiorca, Carlo; Moret, Federica; Martines, Valentina; Tramontano, Daniele; Papassifachis, Maria Alessia; Bini, Simone; Caramazza, Claudia; Fontana, Mario; Lucia, Piernatale; Inghilleri, Maurizio (Frontiers in Medicine, 2022)
Neuromyelitis optica spectrum disorder (NMOSD) is an inflammatory demyelinating disease affecting the central nervous system (CNS), characterized by the triad optic neuritis, transverse myelitis and area postrema syndrome. Antibodies directed against aquaporin-4 (AQP-4), a water channel expressed on the astrocytic membrane, are supposed to play a pathogenic role and are detected in approximately 80% of cases. Clinical signs of NMOSD in elderly patients should arouse the suspicion of paraneoplastic etiology. Herein, we discuss a case of a 76-year-old woman with a 2-month history of confusion, dysarthria and progressive bilateral leg weakness. A whole-body CT scan showed a neoformation of 5 cm in diameter in the median lobe infiltrating the mediastinal pleura; the tumor had already spread to both the upper and lower right lobes, parietal pleura and multiple lymph nodes. Pleural cytology revealed adenocarcinoma cells. The brain MRI documented hyperintense alteration in FLAIR images, involving the anterior portion of the corpus callosum and the periependymal white matter surrounding the lateral ventricles, with mild contrast enhancement on the same areas and on meningeal tissue. T2-weighted spinal cord MRI sequences showed extended signal hyperintensity from bulbo-cervical junction to D7 metamer, mainly interesting the central component and the gray matter. Cerebrospinal fluid analysis revealed no neoplastic cells. Serum AQP-4 IgG antibodies were found. Meanwhile, the patient rapidly developed progressive paraparesis and decreased level of consciousness. High-dose intravenous methylprednisolone therapy was started but her conditions rapidly deteriorated. No other treatment was possible.